Evaluation of the Coupling Coordination Between Energy Low Carbonization and the Socioeconomic System in China Based on a Comprehensive Model - Xin Li; Yuchen Lu; Jingjing Chen; Lihong Peng; Xiaochou Chen (Energies)
Reducing carbon emissions while ensuring economic growth has become a realistic demand in China. The ideal scenario would be to realize the coupling and coordination of the economic and energy systems. This research constructs a coupling coordination evaluation system that objectively reflects the low-carbon energy system (LCES) and socioeconomic system of China. The LCES level has increased to varying degrees in all provinces, with significant differences across regions. The coupling degree of the 30 provinces is between 0.5955 and 0.9999, belonging to the running-in stage and high-coupling stage. Moreover, the average coupling coordination degree (CCD) is 0.3–0.4, belonging to moderate incoordination. In terms of sub-provinces, the CCDs in all provinces indicate high coupling with varying degrees of coordination. Only Qinghai falls into the running-in low-incoordination category. Reaching the 2030 carbon intensity reduction target would be challenging under the baseline scenario. However, this target is expected to be achieved under two scenarios in which the policy constraints of each province are realized. Based on these conclusions, this research proposes a regionally differentiated low-carbon synergistic development strategy to provide a targeted regional synergistic path for the realization of carbon emission reduction and dual-carbon goals in China during the stage of high-quality development.